The Influence of Using Story Dice Media On Students' Critical Reasoning Ability in Learning Indonesian Language Class IV SDN 1 Cimara - Cici Sri Melati; Agatha Kristi Pramudika Sari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: This research is motivated by the importance of developing students' critical thinking skills in learning Indonesian, especially in the 21st-century education era which demands good thinking skills from students. Aim: The purpose of this study is to explore the influence of using storytelling dice media on the critical thinking skills of fourth-grade students at SDN 1 Cimara. Method: The method used is a quantitative approach with a quasi-experimental design and Nonequivalent Control Group Design, involving 39 students selected through purposive sampling. Fourth-grade students at SDN 1 Cimara were used as the experimental class using storytelling dice media, while fourth-grade students at SDN 3 Sukarapih served as the control class without the media. Data were collected through observations and tests (pre-test and post-test) to measure students' critical thinking skills. Result and Discussions: The results of the analysis showed that the pre-test scores of the experimental class were normally distributed, while those of the control class were not. The homogeneity test showed homogeneous variance. Hypothesis testing using the Mann-Whitney U test indicated no influence of storytelling dice media on the pre-test, but a significant influence on the post-test. The average post-test score of the experimental class (87. 81) was higher than that of the control class (60. 22), indicating that storytelling dice media is effective in improving students' critical thinking skills. The discussion of the research results emphasizes that the use of storytelling dice media can increase student engagement and interest in learning Indonesian, and address the problems of traditional one-way teaching methods. Conclusion: The conclusion of this study is that storytelling dice media is an effective tool for enhancing students' critical thinking skills, and further exploration of innovative teaching methods is needed to improve educational outcomes.